PERENCANAAN GEDUNG BANK 6 LANTAI DENGAN MENGGUNAKAN STRUKTUR BETON BERTULANG TAHAN GEMPA - Wawan -; Gatot Setya Budi; Erwin Sutandar (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2022)
The planning of 6-story OCBC bank building using reinforced concrete structure resist to earthquake that located on Jendral Ahmad Yani Street, RT 003 / RW 14, Pontianak city. This building planning is refer to valid standards those are SNI 2847:2019 and SNI 1726:2019. Based on earthquake analysis, this planned building need to be design by using special moment resisting frame system (SMRF) that applying strong column weak beam concept for safety by failing of the beam first compared to the column. Structure analysis assisted by structural analysis software. Based on the calculation, the slab is reinforced concrete with 120 mm for it’s thickness by using wiremesh M8-150, M10-150, and M12-150. Reinforced concrete beam’s dimensional are (400x1000), (350x700), (300x600), (250x500), (250x400), (200x400), and (150x300), meanwhile the diameter of longitudinal reinforcement bar are D22, D19, D16, D13, and D10, and diameter of transverse reinforcement bar are Ø10 and Ø8. The dimensional of reinforced concrete column are (700x700), (600x600), and (500x500) by using D19 longitudinal reinforcement bar and diameter of transverse reinforcement bar are Ø12 and Ø10. The plan of pile cap dimension are (2300x2300x900), (1600x2300x800), (1600x1600x700), and (900x1600x600) by using D13 and D19 as the reinforcement bar.